Bank stability and dividend policy - Dung Viet Tran (Taylor & Francis Group, 2021)
Relying on a US bank sample, we document the double-edged sword of dividends on the bank's riskiness. Paying dividends exposes banks to stricter market discipline, then decreases the risk-taking behaviors of bank management compared with non-payers, consistent with the Dividend-Stability Channel. However, among banks that pay dividends, excessive dividends makes them riskier, consistent with the Dividend-Fragility Channel. Our results remain unchanged due to a battery of robustness testings.